The role of the state in the entrepreneurship ecosystem: insights from Germany - Georg Fuerlinger; Ulrich Fandl; Thomas Funke (Triple Helix, 2015)
The performance of new ventures is strongly impacted by something much larger than the business itself: the surrounding ecosystem. In this network of actors, the role of the state has been underestimated up to this point. This article investigates the nature and composition of the German entrepreneurship ecosystem and suggests a new framework for assessing the role of the state in the entrepreneurial ecosystem. This framework is applied using data from a meta-analysis of existing research as well as qualitative interviews to assess the government influence on the different phases of the science-based innovation process. By analyzing different public initiatives in Germany, this paper provides insights into how governments can influence the attractiveness of an ecosystem, but it also highlights various improvement opportunities. Germany already features a dynamic entrepreneurship ecosystem and has a distinct political agenda to promote entrepreneurship. Improvements have been made in the regulatory environment and in entrepreneurship education, especially tertiary education, and publicly funded programs support the early stages of new ventures. The incentive schemes for scientific staff should be aligned to encourage more tech transfer activities, and more later stage financing is needed, through the involvement of private investments, in order to exploit the full growth potential of new ventures. Germany also needs policies that affect social values and attitudes towards entrepreneurship in order to reduce the stigma of failure and enhance the appreciation of entrepreneurial activity in the society.
Keywords: 330; Innovation; Entrepreneurship ecosystems; Framework; Government support; New venture creation